Pedagogies of the minor gesture: Artful mentorship in college teaching. Issue 1 (1st March 2019) - Flint, Maureen A.; Guyotte, Kelly W.
We, the two authors, found ourselves together in spring semester 2018 as Maureen enrolled in a mentored teaching course with Kelly. It was through this experience that we both became attuned to what Erin Manning termed minor gestures – an attentiveness to the subtleties, nuances, the potential in the minute and often imperceptible rhythms of professional and artistic practice. Through contemplation of the minor gestures of our mentored relationship, we entangle our uncertainties, frustrations, joys and realizations of teaching together, an awakeness to the minor pedagogical movements of the classroom. Moving between poetic reflections, writing and visual imagery in this article, we seek to slow down and dwell in the in-between spaces of research-artfulness-teaching that we have come to know as pedagogical minor gestures. Though minor in name, such gestures linger with us indefinitely as we consider the futures of our professional practices.